On the Prospects of the National Economy after the Accession of the Republic of Bulgaria to the European Union - Marinov, Velko (UNWE Yearbook, 2005)
The paper is an attempt to analyze the opportunities and risks for the Bulgarian economy after the country’s accession to the European Union (EU).The analysis of the historical development of relations between Bulgarian and EU in the context of radical socio-political and economic transformation in our country enables a conclusion that the EU has become a principal foreign economic partner of Bulgaria. The upward trend in the relations between Bulgaria and EU has resulted in a number of serious problems.A critical assessment of the degree of Bulgaria’s readiness to join the EU underlies the inference that the first 2-3 years after the accession are likely to see great risks for our economy.Certain basic requirements for the policy to be pursued by Bulgaria as an EU member have been formulated. The author argues that Bulgaria needs an active macroeconomic policy with the main priority on providing steady rates of economic growth as a precondition for overcoming huge economic, technological and social backwardness of the country. In order to achieve a successful implementation of the accelerated economic growth policy the latter should be complemented by efficient national policies in a number of other areas – investment, attracting direct foreign investment, research and technological development, education, and personnel training.